Digital Competence of the Teacher in the Paraguayan Context (Docentes 2.0 Journal, 2021)
Today's society is changing; this requires teachers to use different strategies to achieve comprehensive preparation. In this sense, the introduction of Information and Communication Technologies (ICT) is considered an indispensable factor for this thorough preparation. Like the other Latin American countries, Paraguay has developed approaches and proposals in different areas to advance the process of incorporating these technologies in education, for which the development of digital skills is essential. The objective of this study was to describe what actions have been undertaken development of teaching digital competencies in Paraguay from 2012 to 2020. A descriptive bibliographic methodology was used, through which was searched for information in various databases. Data, nationally and internationally. The results show that, although Paraguay is not a country at the forefront concerning the exposed issue, efforts are being made to innovate and incorporate this technology in education through teacher training programs while providing this technology to educational institutions. However, there is an urgent need for more solid training for teachers in the technological and pedagogical aspects of professional work.
Keywords: Paraguay; teacher training; digital competence; innovation